Analisis Vegetasi dan Indeks Keanekaragaman Gulma pada Budidaya Kacang Tanah di Desa Ujung Tanoh Darat, Meureubo, Kabupaten Aceh Barat - Hilmina Itawarnemi; Rayhan Amadius Weihan; Chairudin Chairudin; Siti Aminah (Jurnal Agrotek Lestari, 2025)
ABSTRACTThe presence of weeds in peanut cultivation areas can cause a decline in productivity. In Ujong Tanoh Darat Village, farmers do not use mulch in peanut cultivation, making them more susceptible to weeds and greatly affecting crop yields. This study aims to identify the types and diversity of weeds in peanut cultivation fields in Ujong Tanoh Darat Village. The research location was selected using purposive sampling. Data collection was carried out using the quadrat method by placing 10 plots measuring 0.5 m2 x 0.5 m2 randomly. Seven weed species were found in peanut cultivation fields, including Melochia corchorifolia L., Eleusine indica, Spermacoce latifolia, Ludwigia octovalvis, Cyperus sphacelatus Rottb., Paspalum paniculatum L., and Echinochloa crus-galli L. Eleusine indica (SDR 46.98%) and Melochia corchorifolia (SDR 27.30%) were found to have the highest dominance levels, while Paspalium paniculatum L (SDR 3.27%) had the lowest. The diversity index (H' = 1.356) and weed evenness (E = 0.697) indicated moderate diversity with uneven population distribution. Meanwhile, the species richness index (Dₘg = 1.27) was low due to the dominance of certain species. This condition confirms that the presence of dominant weeds has the potential to significantly reduce peanut productivity, so control needs to be focused on sustainable strategies through an Integrated Weed Management (IWM) approach that combines mechanical, cultural and chemical methods selectively.Keywords: Diversity, Eleusine indica, Peanuts, Vegetation Analysis, Weeds